Automatic analysis model of power grid infrastructure project cost level. Issue 5 (January 2021) - Lin, Yubin; Hu, Zhenda; Zhang, Chengwei; Fu, Benzhao; Zhang, Shiming; Hua, Xiaolu
Abstract: Under the development of large-scale power grid investment, precise investment management has important guiding significance for improving power grid investment control and efficiency. In this paper, combined with the current situation of power grid infrastructure project cost management and pricing, using the ABC prediction method, through the analysis of cost price mode and characteristics, the cost theory and method innovation and application are carried out. This method is innovative and verified by experiments.